The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.5012/bkcs.2010.31.6.1589
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study of the Visible Light-Induced Sonophotocatalytic Degradation of MB Solution in the Presence of Fe/TiO2-MWCNT Catalyst

Abstract: In order to effective degradation of organic dye both under visible light or ultrasonic irradiation, the MWCNTs (multiwalled carbon nanotube) deposited with Fe and TiO2 were prepared by a modified sol-gel method. The Fe/TiO2-MWCNT catalyst was characterized by surface area of BET, scanning electron microscope (SEM), Transmission Electron Microscope (TEM), X-ray diffraction (XRD), and energy dispersive X-ray (EDX) and ultraviolet-visible (UV-vis) spectroscopy. The low intensity visible light and low power ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…There were significant differences in crystallite sizes with increasing amounts of DWCNTs in the nanocomposites (Table 1). Similar studies on Fe/TiO 2 -MWCNT composites reported average crystallite size of 5 nm [29]. Optical properties of the nanocomposites are shown in Figure 4(a).…”
Section: Resultssupporting
confidence: 73%
“…There were significant differences in crystallite sizes with increasing amounts of DWCNTs in the nanocomposites (Table 1). Similar studies on Fe/TiO 2 -MWCNT composites reported average crystallite size of 5 nm [29]. Optical properties of the nanocomposites are shown in Figure 4(a).…”
Section: Resultssupporting
confidence: 73%
“…On the other hand, hydroxyl radicals generated via the sonocatalysis is easily transferred to the surface of the ZnO-biosilica nanocomposite, degrading the adsorbed MB molecules. In fact, the immobilized ZnO nanostructures create photoactive centers for the generation of e À /h + pair, whereas the biosilica supplies active adsorption sites in the vicinity of the sonocatalyst [28,30]. This enhances the potential of the sonocatalyst to efficiently adsorb both dye molecules and the light irradiation produced during the cavitation.…”
Section: The Contribution Of Each Process Involved In the Sonocatalysismentioning
confidence: 97%
“…With increasing the initial pH, the surface of the sonocatalyst will be deprotonated, enhancing the attraction force between the cationic dye and negatively charged sonocatalyst. As an another reason, the generation of OH Å radicals as a result of the reaction between the generated h + and OH À ions will be increased at basic conditions [28]. Besides, the sharp decrease in color removal (%) at strong acidic pH (pH = 3) may be due to the corrosion of the sonocatalyst in acidic conditions.…”
Section: Effect Of the Initial Phmentioning
confidence: 98%
See 1 more Smart Citation
“…In the case of a nanosized Bi 2 Se 3 and TiO 2 nanocrystal line coupled graphene based photcatalyst system, coupling of two such semiconductors has a beneficial role in improving charge separation and extends TiO 2 in response to visible light compared with our previous experiment results. 34) A mechanism for the degradation of pollutants on a Bi 2 Se 3 coupled TiO 2 catalyst under visible light irradiation and ultrasonic irradiation is shown in Fig. 9.…”
Section: Proposed Sonophotocatalysis Mechanismmentioning
confidence: 99%